2017
DOI: 10.18632/oncotarget.16625
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic-RGDyC functionalized liposomes for dual-targeting of tumor vasculature and cancer cells in glioblastoma: An in vitro boron neutron capture therapy study

Abstract: The efficacy of boron neutron capture therapy depends on the selective delivery of 10B to the target. Integrins αvβ3 are transmembrane receptors over-expressed in both glioblastoma cells and its neovasculature. In this study, a novel approach to dual-target glioblastoma vasculature and tumor cells was investigated. Liposomes (124 nm) were conjugated with a αvβ3 ligand, cyclic arginine-glycine-aspartic acid-tyrosine-cysteine peptide (c(RGDyC)-LP) (1% molar ratio) through thiol-maleimide coupling. Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Cilengitide is an antagonist of integrins and preliminary but promising results have suggested that the microenvironment plays a role in glioblastoma progression and that ITGB3 inhibitors can act in a neoadjuvant setting to prevent metastasis rather than reduce tumours once formed [ 65 ]. Recently, other studies have used drugs to target integrin αvβ3 in glioblastoma and more recently in lung cancer [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cilengitide is an antagonist of integrins and preliminary but promising results have suggested that the microenvironment plays a role in glioblastoma progression and that ITGB3 inhibitors can act in a neoadjuvant setting to prevent metastasis rather than reduce tumours once formed [ 65 ]. Recently, other studies have used drugs to target integrin αvβ3 in glioblastoma and more recently in lung cancer [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of iRGD conjugation on DOX uptake and cytotoxicity in the human TNBC cells is possibly due to integrin‐mediated endocytosis of iRGD‐DMTPLN via αv integrins overexpressed on both cell lines 19b,c. In RAW 264.7 macrophages, indistinguishable drug uptake and cytotoxicity between DMTPLN and iRGD‐DMTPLN are ascribed to the lack of αv integrin overexpression …”
Section: Resultsmentioning
confidence: 99%
“…The treatment with iRGD‐DMTPLN resulted in a more reduction in F4/80 positive area compared to DMTPLN treatment, though the difference was not statistically significant (Figure b). Although macrophages do not overexpress αvβ3 integrin, their baseline expression of αvβ3 was reported to enable RGD peptide targeting to reduce TAM recruitment in a murine glioblastoma xenografts model . Thus, in addition to delivering more drugs to the metastatic microenvironment, iRGD‐DMTPLN may also inhibit TAM recruitment, resulting in greater TAM reduction as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The role of integrins in cancer progression has been extensively described, being involved in tumor cell migration, invasion and control of angiogenesis, lymphangiogenesis and inflammation [ 10 , 11 ]. Among integrins, αvβ3 is probably the most strongly involved in the regulation of angiogenesis [ 11 , 13 , 40 ]. It has been reported that, differently from the quiescent endothelium, integrin αvβ3 is highly expressed by tumor-associated vessels, possibly mediating the interaction between endothelial cells and provisional matrix protein, such as vitronectin, fibrinogen and proteolized collagen [ 11 , 15 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%